Addressing The Principle and Challenges of Enforcement and Prosecution Under Universal Jurisdiction: Charting New Pathways for International Justice - Nnawulezi, Uche; Nwaechefu, Hilary; Magashi, Salim Bashir (UI Scholars Hub, 2023)
Remarkably, the principle of universal jurisdiction is increasingly gaining traction in the international justice system as a key aspect of the prosecution of crime globally. Driven primarily by efforts to combat crime, this paper examined the relevance of universal jurisdiction in order to determine its adequacy as a system of international justice. Contextually, the principle of universal jurisdiction emerged as a supplemental component of the international justice system. This paper adopts the doctrinal approach by identifying and analyzing the relevant provisions and challenges of universal jurisdiction. It argues that if regular enforcement is a goal of the emerging international justice system, then universal jurisdiction will be an essential part of the system. The paper found out that the application of universal jurisdiction is saddled with challenges, not because of its reliance on national authorities to enforce international norms but due to the reluctance of those authorities to play this role. It concludes that universal jurisdiction will not become a reliable pillar of the international rule of law until these challenges are properly addressed.